Pentadecanal and pentadecanoic acid coatings reduce biofilm formation of Staphylococcus epidermidis on PDMS. Issue 3 (27th February 2020) - Ricciardelli, Annarita; Casillo, Angela; Corsaro, Maria Michela; Tutino, Maria Luisa; Parrilli, Ermenegilda; van der Mei, Henny C
ABSTRACT: Staphylococcus epidermidis is well known to be one of the major causes of infections related to medical devices, mostly due to its strong capacity to form device-associated biofilms. Nowadays, these infections represent a severe burden to the public health system and the necessity of novel antibacterial strategies for the treatment of these difficult-to-eradicate infections is urgent. The Antarctic marine bacterium Pseudoalteromonas haloplanktis TAC125 was found to be able to produce an anti-biofilm molecule, the pentadecanal, active against S. epidermidis . In this work, we modified one of the most widely used silicone-based polymers, polydimethylsiloxane (PDMS), by adsorption of pentadecanal and its most promising derivative, pentadecanoic acid, on the PDMS surface. The biofilm formation of S. epidermidis RP62A on both untreated and modified PDMS was performed in a parallel plate flow chamber system, demonstrating the capability of the proposed anti-biofilm coatings to strongly reduce the biofilm formation. Furthermore, drug-release capacity and long-term efficacy (21 days) were also proven for the pentadecanoic acid coating. Abstract : The coating obtained by adsorption of pentadecanal and pentadecanoic acid on PDMS reduces the bacterial adhesion and biofilm formation of Staphylococcus epidermidis.